Fuzzy Logic Augmentation of Neural and Optimization Algorithms: Theoretical Aspects and Real Applications - Orozco Rosas, Ulises; Montiel, Oscar; Sepúlveda, Roberto (Springer International Publishing AG, 2018)
Path planning is a fundamental task in autonomous mobile robot navigation and one of the most computationally intensive tasks. In this work, a parallel version of the bacterial potential field (BPF) method for path planning in mobile robots is presented. The BPF is a hybrid algorithm, which makes use of a bacterial evolutionary algorithm (BEA) with the artificial potential field (APF) method, to take advantage of intelligent and classical methods. The parallel bacterial potential field (parallel-BPF) algorithm is implemented on a graphics processing unit (GPU) to speed up the path planning computation in mobile robot navigation. Simulation results to validate the analysis and implementation are provided; the experiments were specially designed to show the effectiveness and the efficiency of the parallel-BPF algorithm.
Parallel Bacterial Potential Field Algorithm for Path Planning in Mobile Robots: A GPU Implementation
Keywords: Bacterial potential field; Path planning; Mobile robots; GPU; Campus Tijuana